AETIOLOGICAL AND PATHOLOGICAL STUDY ON OVINE AND CAPRING ABORTED FOETI - M. AL-Darraji, A.; H. Dhahir, S.; J. Alwan, M. (The Iraqi Journal of Veterinary Medicine, 1992)
Bacteriological and histopathological investigations were conducted on ovine and caprine aborted foeti, ten each, collected from different parts of Iraq, to determine the posible etiology of abortion and to characterize the histopathological changes associated with them. Microbial isolation revealed the following isolates: Brucella melitensis(4), Listeria monocytogens(3), Chlamydia psittaci(2) and Campylobacter foetus"). Histopathological changes were evident in specimens of placenta and aborted foeti. These are: Bacterial colonies in the necrotic chorionic epithelial cells, bronchopneumonia, multifoceal hepatic necrosis, splenic reticuloendothelial hyperplasia and interstitial nephritis were associated with Br. melitensis. isolates.Multifocal necotizing hepatitis, pneumonitis, diffuse reticuloendothelial hyperplasia with lymphoid necrosis in spleen, nephrosis and meningitis were features of C. psittaci isolates. Myocarditis, acute hepatocellular degeneration and necrosis and diffuse cortical renal hemorrhages accompanied the L. monocytogens induced abortion. Multifocal hepatitis and suppurative pneumonia are seen in V. fetus abortion foeti.